分散計算機システムを用いた高速ネットワーク読影支援システム - 松本, 徹; 阿部, 郁男; 滝沢, 穂高; 舘野, 之男; 山本, 眞司; 藤野, 雄一; 飯沼, 武 (Journal of Computer Aided Diagnosis of Medical Images, 2003)
In this paper, we describe an efficient network computer-aided diagnosis system equipped with distributed computers. Two experimental results are shown to evaluate the efficiency of our new system. Ones are translation times of sample CT images using our exclusive global network. The others are calculation times of cancer shadow recognition using distributed computer systems. 本論文では，分散計算機システムとグローバルネットワークとを統合した高速ネットワーク診断支援システムについて述べる．本システムの有効性を評価するための指標として，ネットワークを用いた画像転送実験と，分散計算機システムを用いた読影実験の結果を示す．